Preparation method of chopped carbon fiber reinforced ceramic-based crucible material

By using a multi-step treatment method of chopped carbon fiber and ceramic matrix in ceramic-based crucible materials, the problems of easy damage and unstable performance of traditional ceramic-based crucible materials under harsh conditions are solved, and the high mechanical properties, thermal shock resistance and long-term service life of the material are improved.

CN119591415APending Publication Date: 2025-03-11DEBAO CARBON CERAMICS (SUZHOU) TECH CO LTD

Patent Information

Application Number
CN202411765082.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Traditional ceramic-based crucible materials are prone to damage under harsh conditions such as high temperature, high pressure and chemical corrosion, and have a high thermal expansion coefficient, and the thermal stress can easily aggravate the material damage. Combined with uneven interface processing, local performance imbalance, uneven sintering, microcracks and pore defects, etc., affecting service life and stability.

Method used

The interfacial bonding between chopped carbon fiber and ceramic matrix powder is adopted for dry mixing, wet mixing and ball milling, drying, cold pressing molding, degreasing and high-temperature sintering, and the interface bonding between carbon fiber and ceramic matrix is ​​enhanced through surface treatment and coating technology to ensure uniform distribution and high-density bonding.

Benefits of technology

It significantly improves the mechanical properties, thermal shock resistance and service life of the material, reduces sintering defects and thermal stress damage, enhances the density and stability of the material, and adapts to long-term use in high temperature and harsh chemical environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591415A_ABST
    Figure CN119591415A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a chopped carbon fiber reinforced ceramic-based crucible material, and relates to the technical field of chopped carbon fiber reinforced ceramic-based crucible materials.The preparation method comprises the following steps that S1, chopped carbon fibers and ceramic matrix powder are subjected to dry mixing according to a preset proportion, and the chopped carbon fibers are preliminarily and evenly distributed in the ceramic matrix powder; s2, the carbon fibers obtained after dry mixing and ceramic matrix powder are mixed through a wet method, ball milling or homogenizing treatment is carried out in a liquid medium, the carbon fibers and the ceramic matrix powder are fully dispersed, and mixed slurry is obtained.According to the preparation method, oxidation treatment or acid pickling treatment or a metal coating technology is carried out on the surfaces of the short carbon fibers; according to the invention, the carbon fibers are added into the ceramic matrix, so that the interface bonding force between the carbon fibers and the ceramic matrix is obviously improved, the carbon fibers are uniformly dispersed in the ceramic matrix, the agglomeration problem of the carbon fibers is avoided, and the mechanical properties, including compressive strength, bending strength and thermal shock resistance, of the material are enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of chopped carbon fiber reinforced ceramic-based crucible materials, and in particular to a method for preparing a chopped carbon fiber reinforced ceramic-based crucible material. Background Art

[0002] Ceramic-based crucible materials are widely used in processes such as high-temperature smelting, chemical reactions, and material purification, and usually need to be used under harsh conditions such as high temperature, high pressure, and chemical corrosion. Traditional ceramic-based crucible materials are mainly based on a single ceramic material, such as alumina, silicon carbide, and zirconium oxide. Although these materials have good resistance to high temperatures and chemical corrosion, they are relatively brittle, and their mechanical properties, especially thermal shock resistance, are relatively poor. They are prone to cracks and material breakage during frequent rapid temperature changes. In addition, under high temperature conditions, ceramic materials have a high coefficient of thermal expansion and are prone to thermal stress, further exacerbating the risk of material damage. In traditional crucible preparation processes, the combination of ceramic matrix and reinforcing fibers usually lacks an effective interface treatment process. Reinforcing materials such as carbon fibers are unevenly distributed in the ceramic matrix, and are prone to forming agglomeration areas, resulting in an imbalance in local material properties, which in turn affects the mechanical properties of the overall crucible. Due to the relatively rough process control in the mixing and molding process in the traditional process, the material is prone to uneven sintering, microcracks and pore defects in the subsequent sintering process. Especially during high-temperature sintering, due to the lack of precise temperature control, the sintering density of the material is insufficient and the microstructure is unstable, resulting in a shortened service life of the final product. In addition, the traditional crucible surface treatment process is limited and cannot effectively enhance the corrosion resistance and oxidation resistance of the material. During long-term use, the surface is prone to oxidation and corrosion, which further reduces the service life and stability of the material and needs to be optimized and improved. Summary of the invention

[0003] The purpose of the present invention is to solve the technical problems raised in the above background technology.

[0004] The present invention adopts the following technical solution: a method for preparing a chopped carbon fiber reinforced ceramic-based crucible material, comprising the following steps:

[0005] S1: Dry mixing of carbon fiber and ceramic powder: dry mixing the chopped carbon fiber and the ceramic matrix powder in a predetermined ratio, so that the chopped carbon fiber is initially evenly distributed in the ceramic matrix powder;

[0006] S2: Wet mixing and ball milling: The dry-mixed carbon fiber and ceramic matrix powder are wet mixed and ball milled or homogenized in a liquid medium to fully disperse them to obtain a mixed slurry;

[0007] S3: slurry drying: drying the mixed slurry to remove the liquid medium and obtain dry powder;

[0008] S4: cold pressing: the dry powder is pressed and formed by a cold pressing process to obtain a crucible green body;

[0009] S5: Degreasing: Degreasing the green crucible to remove the binder or molding agent added during the mixing and molding process;

[0010] S6: High temperature sintering: The degreased green body is sintered at high temperature in an inert gas or vacuum environment to tightly combine the carbon fiber and the ceramic matrix material;

[0011] S7: Surface treatment: Surface treatment or finishing is performed on the sintered crucible material to improve its surface quality.

[0012] Preferably, the mass ratio of the chopped carbon fiber to the ceramic matrix powder in S1 is 1:99 to 30:70, wherein the length of the chopped carbon fiber is 3 mm to 15 mm, the diameter is 5 μm to 10 μm, and the surface of the carbon fiber is treated, the surface treatment includes oxidation treatment, pickling treatment or coating of a metal coating by chemical deposition, the metal coating material is selected from nickel, titanium or copper, and the liquid medium used in the wet mixing process in S2 is deionized water, ethanol or acetone, the mixing time is 1 to 4 hours, the ball-to-material ratio is 1:2 to 1:6, and a dispersant is added during this process, and the mass of the dispersant is 0.1% to 2% of the total mass of the mixed slurry. Here, by limiting the length, diameter and surface treatment (oxidation, pickling or metal coating) of the chopped carbon fiber, the interfacial bonding force between the carbon fiber and the ceramic matrix is ​​improved, the uniform distribution of the carbon fiber in the ceramic matrix is ​​ensured, the agglomeration of the carbon fiber is reduced, and the mechanical properties and thermal shock resistance of the material are further improved. The liquid medium and mixing parameters of wet mixing control the uniformity of the mixing process, and the use of dispersants helps to enhance the stability of the material and ensure good dispersion of carbon fiber and ceramic powder.

[0013] Preferably, the drying step in S3 is carried out by spray drying or vacuum drying process, the spray drying temperature is 80°C to 150°C, the drying time is 1 to 5 hours, the moisture content of the obtained dry powder is less than 1%, and it has uniform particle fluidity, the pressure range of the cold pressing step in S4 is 100 MPa to 400 MPa, the molding time is 5 minutes to 15 minutes, and a molding agent is added during the molding process, the molding agent is polyvinyl alcohol, polyvinyl pyrrolidone or other decomposable organic additives, and the mass of the molding agent is 0.5% to 5% of the total mass of the mixture. Here, by controlling the drying process conditions (such as temperature and time), the fluidity and uniformity of the dry powder are ensured, the defects that may occur in the subsequent molding process of the material are reduced, and the moisture content of the powder is controlled, avoiding the generation of pores or cracks during pressing and sintering. The use of the molding agent not only improves the strength of the crucible green body, but also ensures the compactness of the green body during the molding process. The selection of the molding agent further optimizes the removal of impurities during the degreasing process, which helps the purity and compactness of the final material.

[0014] Preferably, the degreasing treatment in S5 is carried out at a temperature of 300°C to 600°C for 1 to 3 hours. The degreasing treatment is carried out by heating to the target temperature in stages, so that the binder and the molding agent are completely decomposed and volatilized to ensure the smooth progress of the subsequent sintering steps without affecting the density and structural integrity of the material. Here, by reasonably setting the degreasing temperature and time, and adopting a staged heating method, the binder and the molding agent are completely decomposed and volatilized, avoiding the influence of the residue on the material in the subsequent sintering process. The stress concentration phenomenon that may occur during the degreasing process is effectively controlled, ensuring the structural integrity and density of the material in the subsequent sintering stage, and reducing the possibility of defects such as cracks and pores in the material during the sintering process.

[0015] Preferably, the sintering step in S6 is carried out in an inert gas or vacuum environment, the inert gas is selected from nitrogen or argon, the sintering temperature ranges from 1200°C to 1800°C, the heating rate is 2°C / minute to 10°C / minute, the holding time is 2 to 12 hours, and the temperature is cooled at a rate of 1°C / minute to 5°C / minute after sintering to ensure the microstructural stability of the crucible material. Here, by sintering in an inert gas or vacuum environment and reasonably controlling the sintering temperature, heating rate and holding time, the full combination of carbon fiber and ceramic matrix at high temperature is ensured, and the density and stability of the material are improved. The staged cooling procedure further reduces the thermal stress caused by rapid cooling, avoids microstructural damage in the material, and ensures that the material has a longer service life and better performance.

[0016] Preferably, the surface treatment step in S7 includes sandblasting, polishing or plasma spraying, the spraying material is selected from aluminum oxide, silicon carbide or silicon nitride, the coating thickness is 10 microns to 200 microns, and the coating thickness and surface treatment conditions are adjusted to meet the requirements of different application environments. Here, by sandblasting, polishing or plasma spraying the crucible material, combined with the use of coating materials such as aluminum oxide, silicon carbide or silicon nitride, the surface corrosion resistance and oxidation resistance of the crucible material are enhanced, and by adjusting the coating thickness, customized protection can be provided according to different working environment requirements, further improving the adaptability of the crucible material in complex environments.

[0017] Preferably, the ceramic matrix powder used in S1 and S2 is selected from one or more of the following materials: aluminum oxide, zirconium oxide, silicon carbide, silicon nitride, magnesium oxide or titanium oxide, and the particle size of the ceramic matrix powder is 1 micron to 10 microns. The mechanical properties and thermal stability of the material are controlled by selecting the particle size and type of the ceramic powder to adapt to the use requirements of the crucible in different temperatures and chemical environments. Here, the mechanical properties and thermal stability of the crucible material are effectively controlled by selecting the particle size and material type of the ceramic matrix powder. Ceramic powders of different particle sizes can regulate the density and thermal conductivity of the crucible material, and by optimizing the type of ceramic matrix, the crucible material can maintain excellent performance in different temperatures and chemical environments to meet the needs of a variety of industrial applications.

[0018] Preferably, the molding agent in S4 is combined with the degreasing treatment in S5, and the molding agent is polyvinyl alcohol, polyvinyl pyrrolidone or other decomposable organic matter. The decomposition temperature of the molding agent during the degreasing process is 300°C to 600°C, ensuring that the molding agent is completely volatilized during the degreasing stage, and no impurities that affect the sintering process remain, thereby improving the purity of the material and the compactness of the finished product. Here, by combining the molding agent with the degreasing process, the complete decomposition and volatilization of the molding agent during the degreasing stage is ensured, the influence of the molding agent residue on the compactness of the material during the sintering process is avoided, the purity of the material is improved, and the generation of sintering defects is reduced. At the same time, this design optimizes the molding quality of the crucible green body, provides a good foundation for subsequent high-temperature sintering, and further enhances the mechanical properties of the final crucible material.

[0019] Preferably, the sintering process in S6 adopts a staged heating and insulation program, the heating rate in the initial stage is 2°C / minute to 5°C / minute, the insulation stage lasts for 4 to 8 hours, and the sintering is cooled at a rate of 1°C / minute to 5°C / minute. In combination with the surface treatment step in S7, the sintered crucible material is plasma sprayed or sandblasted to adapt the surface-treated crucible material to high temperature and harsh chemical environment. Here, by designing a staged heating and insulation program, the accumulation of thermal stress during the sintering process is reduced, the stability of the internal microstructure of the material is ensured, and the generation of sintering defects is reduced. Combined with subsequent plasma spraying or sandblasting, the crucible material can have stronger oxidation resistance and corrosion resistance in high temperature and harsh chemical environments, further extending its service life and enhancing its performance stability under harsh working conditions.

[0020] Compared with the prior art, the advantages and positive effects of the present invention are:

[0021] 1. In the present invention, by performing oxidation treatment, pickling treatment or metal coating process on the surface of the chopped carbon fiber, the interfacial bonding strength between the carbon fiber and the ceramic matrix is ​​significantly improved, the carbon fiber is evenly dispersed in the ceramic matrix, the agglomeration problem of the carbon fiber is avoided, and the mechanical properties of the material are enhanced, including compressive strength, flexural strength and thermal shock resistance.

[0022] 2. In the present invention, by adopting a reasonable wet mixing and drying process, it is ensured that the carbon fiber and the ceramic matrix are fully dispersed in the mixed slurry, and the dry powder has good fluidity and particle uniformity, which not only improves the density and uniformity of the green body during the cold pressing process, but also effectively reduces the defects in the molding process, providing a good foundation for subsequent high-temperature sintering.

[0023] 3. In the present invention, by carrying out high-temperature sintering in an inert gas or vacuum environment and adopting a staged heating and cooling process, the accumulation of thermal stress and the destruction of the internal structure of the material are prevented, the carbon fiber and the ceramic matrix are fully combined, the density, high temperature resistance and microstructural stability of the material are significantly improved, and ultimately the long-term service life and performance stability of the crucible material are improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The present invention provides a schematic diagram of the overall process of a method for preparing a chopped carbon fiber reinforced ceramic-based crucible material. DETAILED DESCRIPTION

[0025] In order to more clearly understand the above-mentioned purpose, features and advantages of the present invention, the present invention is further described below in conjunction with the accompanying drawings and embodiments. It should be noted that the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.

[0026] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways than those described herein. Therefore, the present invention is not limited to the specific embodiments of the following disclosure.

[0027] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the technical field.

[0028] Embodiment 1

[0029] The present invention provides a technical solution: a method for preparing a chopped carbon fiber reinforced ceramic-based crucible material, first, a nickel-coated chopped carbon fiber with a length of 5 mm and a diameter of 8 microns is dry-mixed with a mixed ceramic matrix powder of alumina and silicon carbide in a ratio of 15:85. The carbon fiber is nickel-coated to enhance its bonding with the ceramic matrix, and the mixing lasts for 30 minutes so that the carbon fiber is evenly distributed in the ceramic matrix. After dry mixing, the mixture is added to deionized water and wet-milled for 2 hours at a ball-to-material ratio of 1:3, and 1% polyvinyl pyrrolidone is added as a dispersant to form a uniform mixed slurry. Next, the slurry is dried at 100°C for 2 hours by a spray dryer, and the moisture content of the obtained dry powder is less than 1%. The dried powder is placed in a mold, cold-pressed at a pressure of 200 MPa for 10 minutes, and 2% polyvinyl alcohol is added as a molding agent to enhance the compactness of the green body. The green body is degreased at 300°C and heated to 500°C in stages for 2 hours to ensure complete decomposition of the molding agent. Subsequently, the green body is sintered at 1600°C in a nitrogen environment for 6 hours at a heating rate of 3°C / min and a cooling rate of 2°C / min. Finally, the surface of the sintered crucible material is polished, and the inner wall of the crucible is plasma sprayed with a 100-micron-thick alumina coating to enhance the anti-oxidation and corrosion resistance of the crucible.

[0030] Embodiment 2

[0031] A method for preparing a chopped carbon fiber reinforced ceramic-based crucible material, first, acid-washed chopped carbon fibers with a length of 8 mm and a diameter of 6 μm are dry-mixed with ceramic matrix powders of zirconium oxide and silicon nitride in a ratio of 10:90, and the mixing time is 45 minutes. The acid-washing treatment removes impurities on the surface of the carbon fiber and enhances the compatibility of the carbon fiber with the ceramic matrix. Subsequently, ethanol is added as a liquid medium, and wet ball milling is performed for 3 hours at a ball-to-material ratio of 1:4, and 0.5% polyvinyl alcohol is added as a dispersant to ensure that the carbon fiber is fully dispersed. Drying at 120°C for 3 hours in a vacuum dryer obtains a powder with uniform particles. The powder is placed in a mold, cold-pressed at a pressure of 300 MPa for 7 minutes, and 3% polyvinyl pyrrolidone is added as a molding agent. The raw crucible is degreased at 400°C, heated to 600°C for 2 hours, and ensures that the molding agent is completely decomposed. The sintering process is carried out in a vacuum environment, the temperature is set at 1400℃, the temperature is kept for 8 hours, the heating rate is 5℃ / minute, and the cooling rate is 4℃ / minute. After sintering, the inner and outer walls of the crucible are sandblasted, and a 50-micron-thick silicon carbide coating is attached to the surface to enhance the wear resistance and thermal shock resistance of the crucible material.

[0032] Embodiment 3

[0033] A method for preparing a chopped carbon fiber reinforced ceramic-based crucible material, first, dry-mixing chopped carbon fibers with a length of 10 mm and a diameter of 6 μm coated with titanium on the surface with magnesium oxide powder in a ratio of 20:80, and the mixing time is 60 minutes to ensure that the carbon fibers are evenly distributed in the magnesium oxide powder. After mixing, acetone is added as a liquid medium, and wet homogenization is performed for 1.5 hours at a ball-to-material ratio of 1:5, and 0.8% of a dispersant is added to ensure that the slurry is uniform. Drying is performed at 90°C for 1.5 hours by a spray dryer to obtain a powder with uniform particles and good fluidity. The powder is placed in a mold and cold-pressed for 12 minutes at a pressure of 150 MPa, and 2% of a molding agent is added during the molding process. The raw crucible is degreased at 500°C for 1.5 hours to ensure that the molding agent is completely volatilized. The degreased raw crucible is sintered at 1500°C in a vacuum environment, and the temperature is kept for 5 hours, with a heating rate of 4°C / minute and a cooling rate of 3°C / minute. After sintering, the inner wall of the crucible is polished, the outer wall is plasma sprayed, and a 100-micron-thick silicon nitride coating is applied to further improve the corrosion resistance and thermal shock resistance of the crucible.

[0034] Embodiment 4

[0035] A method for preparing a chopped carbon fiber reinforced ceramic-based crucible material, first, dry-mixing chopped carbon fibers with a length of 7 mm and a diameter of 7 μm with ceramic matrix powders of alumina and zirconia in a ratio of 20:80, and the mixing time is 40 minutes to ensure that the carbon fibers are evenly distributed in the ceramic matrix powder. The surface of the carbon fibers is treated with nitrogen plasma to enhance the interfacial bonding between the carbon fibers and the ceramic matrix. The dry-mixed mixture is added to deionized water, and wet ball milling is performed at a ball-to-material ratio of 1:3 for 2.5 hours, and 1.2% polyvinyl pyrrolidone is added as a dispersant to ensure that the carbon fibers are evenly dispersed in the slurry. The slurry is dried at 110°C for 2.5 hours in a vacuum dryer, and the dried powder has good fluidity and uniform particle size. The powder is cold-pressed in a mold at a pressure of 250 MPa for 10 minutes, and 2.5% polyvinyl alcohol forming agent is added to ensure the strength and density of the raw crucible. The raw crucible is degreased in stages at 400°C for 2 hours to ensure that all the molding agents are completely decomposed and volatilized. Subsequently, the raw crucible is sintered at high temperature in an argon environment at a temperature of 1700°C for 5 hours at a heating rate of 4°C / minute. After sintering, the temperature is cooled at a rate of 3°C / minute. The inner and outer walls of the sintered crucible material are sandblasted, and a 70-micron-thick zirconium oxide coating is applied to the surface of the crucible to further improve the high temperature resistance and corrosion resistance of the crucible material, making it suitable for high-temperature metal smelting and long-term use in complex chemical environments.

[0036] The above description is only a preferred embodiment of the present invention and does not limit the present invention in other forms. Any technician familiar with the profession may use the technical content disclosed above to change or modify it into an equivalent embodiment with equivalent changes and apply it to other fields. However, any simple modification, equivalent change and modification made to the above embodiment based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a chopped carbon fiber reinforced ceramic-based crucible material, characterized in that: The following steps are involved: S1: Dry mixing of carbon fiber and ceramic powder: dry mixing the chopped carbon fiber and the ceramic matrix powder in a predetermined ratio, so that the chopped carbon fiber is initially evenly distributed in the ceramic matrix powder; S2: Wet mixing and ball milling: The dry-mixed carbon fiber and ceramic matrix powder are wet mixed and ball milled or homogenized in a liquid medium to fully disperse them to obtain a mixed slurry; S3: slurry drying: drying the mixed slurry to remove the liquid medium and obtain dry powder; S4: cold pressing: the dry powder is pressed and formed by a cold pressing process to obtain a crucible green body; S5: Degreasing: Degreasing the green crucible to remove the binder or molding agent added during the mixing and molding process; S6: High temperature sintering: The degreased green body is sintered at high temperature in an inert gas or vacuum environment to tightly combine the carbon fiber and the ceramic matrix material; S7: Surface treatment: Surface treatment or finishing is performed on the sintered crucible material to improve its surface quality.

2. The method for preparing a chopped carbon fiber reinforced ceramic-based crucible material according to claim 1, characterized in that: The mass ratio of the chopped carbon fiber to the ceramic matrix powder in S1 is 1:99 to 30:70, wherein the length of the chopped carbon fiber is 3 mm to 15 mm, the diameter is 5 μm to 10 μm, and the surface of the carbon fiber is treated, and the surface treatment includes oxidation treatment, pickling treatment or coating of a metal coating by chemical deposition, and the metal coating material is selected from nickel, titanium or copper. In the wet mixing process in S2, the liquid medium used is deionized water, ethanol or acetone, the mixing time is 1 to 4 hours, the ball-to-material ratio is 1:2 to 1:6, and a dispersant is added during this process, and the mass of the dispersant is 0.1% to 2% of the total mass of the mixed slurry.

3. The method for preparing a chopped carbon fiber reinforced ceramic-based crucible material according to claim 1, characterized in that: The drying step in S3 is carried out by spray drying or vacuum drying process, the spray drying temperature is 80°C to 150°C, the drying time is 1 to 5 hours, the moisture content of the obtained dry powder is less than 1%, and the particle fluidity is uniform. The pressure range of the cold pressing molding step in S4 is 100 MPa to 400 MPa, the molding time is 5 minutes to 15 minutes, and a molding agent is added during the molding process. The molding agent is polyvinyl alcohol, polyvinyl pyrrolidone or other decomposable organic additives, and the mass of the molding agent is 0.5% to 5% of the total mass of the mixture.

4. The method for preparing a chopped carbon fiber reinforced ceramic-based crucible material according to claim 1, characterized in that: The debinding process in S5 is carried out at a temperature of 300°C to 600°C for a duration of 1 to 3 hours. The debinding process is carried out by heating the temperature to the target temperature in stages so that the binder and the molding agent are completely decomposed and volatilized to ensure the smooth progress of the subsequent sintering step without affecting the density and structural integrity of the material.

5. The method for preparing a chopped carbon fiber reinforced ceramic-based crucible material according to claim 1, characterized in that: The sintering step in S6 is carried out in an inert gas or vacuum environment, the inert gas is selected from nitrogen or argon, the sintering temperature ranges from 1200°C to 1800°C, the heating rate is 2°C / min to 10°C / min, the holding time is 2 to 12 hours, and after the sintering is completed, the temperature is lowered at a rate of 1°C / min to 5°C / min to ensure the microstructural stability of the crucible material.

6. The method for preparing a chopped carbon fiber reinforced ceramic-based crucible material according to claim 1, characterized in that: The surface treatment step in S7 includes sandblasting, polishing or plasma spraying, the spraying material is selected from aluminum oxide, silicon carbide or silicon nitride, the coating thickness is 10 microns to 200 microns, and the coating thickness and surface treatment conditions are adjusted to meet the requirements of different application environments.

7. The method for preparing a chopped carbon fiber reinforced ceramic-based crucible material according to claim 1, characterized in that: The ceramic matrix powder used in S1 and S2 is selected from one or more of the following materials: aluminum oxide, zirconium oxide, silicon carbide, silicon nitride, magnesium oxide or titanium oxide. The particle size of the ceramic matrix powder is 1 micron to 10 microns. The mechanical properties and thermal stability of the material are controlled by selecting the particle size and type of the ceramic powder to adapt to the use requirements of the crucible in different temperatures and chemical environments.

8. The method for preparing a chopped carbon fiber reinforced ceramic-based crucible material according to claim 1, characterized in that: The molding agent in S4 is combined with the degreasing treatment in S5. The molding agent is polyvinyl alcohol, polyvinyl pyrrolidone or other decomposable organic matter. The decomposition temperature of the molding agent during the degreasing process is 300°C to 600°C, ensuring that the molding agent is completely volatilized during the degreasing stage without residual impurities that affect the sintering process, thereby improving the purity of the material and the density of the finished product.

9. The method for preparing a chopped carbon fiber reinforced ceramic-based crucible material according to claim 1, characterized in that: The sintering process in S6 adopts a staged heating and insulation program, with a heating rate of 2°C / min to 5°C / min in the initial stage, a insulation stage duration of 4 to 8 hours, and a cooling rate of 1°C / min to 5°C / min after sintering. Combined with the surface treatment step in S7, the sintered crucible material is plasma sprayed or sandblasted to make the surface-treated crucible material adapt to high temperature and harsh chemical environment.

Citation Information

Patent Citations

  • Preparation method of short fiber reinforced silicon carbide ceramics containing silicon dioxide

    CN104876614A

  • Manufacturing method of quartz ceramic crucible

    CN114230323A

  • Carbon / carbon composite material crucible containing aluminum oxide coating and silicon carbide coating

    CN114455982A

  • Silicon carbide ceramic product, preparation method thereof and silicon carbide ceramic crucible side

    CN117105666A

  • Chopped fiber reinforced ultra-high temperature ceramic matrix composite material and preparation method thereof

    CN118666586A

Cited By

  • High-strength silicon nitride ceramic material and preparation method thereof

    CN120365082A